MAINTENANCE OF LIBRARY USERS IN ELECTRONIC ENVIRONMENT - Krainuk, Olena V. (University Library at a New Stage of Social Communications Development. Conference Proceedings, 2019)
It is given the analysis of basic normative documents, which are the basis for practical realization of processes of user maintenance in electronic environment.